The Effectiveness of Using Visual Dictionary to Teach Vocabulary at the Grade Students - Rahma Novia Anggraeni; Abdul Ngafif; Zulia Chasanah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2021)
This basic problem comes to the students’ low vocabulary mastery, teacher’s low creativity in teaching, infectivity of general dictionary to teach vocabulary, teacher’s low creativity in teaching, infectivity of vocabulary teaching and learning methods currently applied, students tend to get bored in learning vocabulary because of the use of monotonous methods. This fundamental problem then lead the researchers to do research which goal is to find out in which using visual dictionary more effective in teaching vocabulary for junior high school. By applying quantitative research, the researchers did research in SMPN 36 Purworejo. Employing Class 8 A taught using visual dictionaryand Class 8 C taught using general dictionary, the researchers then give 20 questions of multiple choice test to evaluate the result of teaching vocabulary. The result of this research shows that the mean score of 8 A is 81.96 and the mean of 8 C is 74.24. Then, from the computation of inferential analysis, it shows that the result of Zvalue(6.98) is lower than Ztable (1.96).From the result, it can be concluded that use of Visual Dictionary in teaching vocabulary skill at the eighth grade is effective.